Comercial yeast samples DNA extraction using universal kit - Robiatush Sholichah Arrohmah; Radinal Kautsar (Genbinesia Journal of Biology, 2021)
Yeast is a microorganism that is relatively difficult to obtain its DNA mass. This is caused by the content of cell walls with a thick and rigid composition, such as chitin. This study aims to provide information on the best concentration and purity of the DNA extraction results of various types of commercial yeast in different samples weight. The method used is based on Universal Kit procedure with modification. This study indicates that differences in concentration or sample weight do not affect the DNA concentration and purity ratio value of each yeast sample. Each best result obtained from Jago (Rhizopus oligosporus), Raprima (Rhizopus oligosporus) and Fermipan (Saccharomyces cerevisiae) in 50 mg sample, NKL (Saccharomyces cerevisiae) yeast in 40 mg. Recomendation weight samples to extract DNA of Rhizopus oligosporus and Saccharomyces cerevisiae isolates are between 40 mg to 50 mg. The contamination factor causes the difference in the value of purity in each sample during DNA extraction.